Evaluation of Effect of Homoeopathic Mother Tincture of Tinospora Cordifolia in STZ Induced Diabetic Nephropathy in Rats (Advancements in Homeopathic Research, 2024)
Background: Diabetes mellitus has been known to  mankind since antiquity as a “Honeyed Urine” disease  in ancient literature, “Madhu-Meh” in Hindi, and  “Sugar disease” in layman's language. This research  evaluates the therapeutic potential of a homoeopathic  Mother Tincture derived from Tinospora cordifolia for treating diabetic nephropathy. The study began  with phytochemical screening and standardization  of the plant extract. Subsequently, its antioxidant  and anti-diabetic properties will be evaluated in  vivo. Finally, the research will induce and assess  the Homoeopathic Mother Tincture’s ability to  mitigate the complications associated with diabetic  nephropathy.  Method: This study investigates the potential of a  mother tincture in preventing diabetic nephropathy  in rats. Rats were divided into groups of 6, and  diabetes was induced by injecting Streptozotocin  (STZ) followed by nicotinamide to prevent severe  hypoglycemia. Only rats with a fasting blood glucose  level ≥250 mg/dl after 72 hours were included.  Different doses of the mother tincture (100, 200,  and 400 mg/kg) were selected based on reported  oral acute toxicity studies, and the development of  diabetic nephropathy was assessed by measuring  elevated serum urea, uric acid, creatinine, and BUN  levels. Result: Tinospora cordifolia has been shown to  significantly reduce blood glucose levels, food and  water intake, creatinine levels, uric acid levels, and  triglycerides. Conclusion: This study observed significant  reductions in Sugar Levels using Mother Tincture of  Tinospora cordifolia for diabetic nephropathy. These  encouraging findings warrant further investigation  due to limitations. Therefore, we recommend larger,  longer-duration studies to confirm efficacy and safety  for managing diabetic nephropathy.
Keywords: Diabetic Nephropathy; Tinospora Cordifolia; Mother Tincture; Homoeopathy